2012
DOI: 10.1089/cap.2011.0051
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Culturally Diverse Children and Adolescents with Depression

Abstract: This article is written for the practitioners treating depression in ethnic minority youth. It will review the context in which services are delivered to these youth: Researchers have recognized persistent ethnic differences in terms of utilization of services and unmet need. Furthermore, when ethnic minority youth do receive pediatric mental health care, the services that they receive may differ from those given to White patients. The reasons for these discrepancies have been examined in numerous studies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…One of the most recognized factors associated with health disparities is the problem of poor communication with parents/caretakers. Poor communication prevents them from receiving health benefits, participating in research studies, and actively contributing to disease prevention and health care for their children (69). Decades of effort and research on strategies to reduce health disparities have led to inconclusive and conflicting results, and there has been little improvement in leading health indicators (10).…”
mentioning
confidence: 99%
“…One of the most recognized factors associated with health disparities is the problem of poor communication with parents/caretakers. Poor communication prevents them from receiving health benefits, participating in research studies, and actively contributing to disease prevention and health care for their children (69). Decades of effort and research on strategies to reduce health disparities have led to inconclusive and conflicting results, and there has been little improvement in leading health indicators (10).…”
mentioning
confidence: 99%
“…39,41,42 Results show that parental appraisal of emotional and behavioral difficulties in children is the most salient factor influencing mental health services and the only variable that is significant across all racial/ethnic groups. This is congruent with prior literature.…”
Section: Discussionmentioning
confidence: 96%
“…This type of mental health service gap is especially pronounced for internalizing behaviors because it has been observed that Hispanic children often do not perceive “feeling depressed or afraid” as rationale for treatment (Cummings, Case, Ji, Chae, & Druss, ). Research has identified multilevel barriers to mental health services in Hispanic families including financial constraints, transportation issues, lack of mental health services in the neighborhood, limited English language fluency, low health literacy, and persistent stigmas against mental health (Bear, Finer, Guo, & Lau, ; Stewart, Simmons, & Habibpour, ; Uebelacker et al., ). School‐based programs have the potential to reduce these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…services in the neighborhood, limited English language fluency, low health literacy, and persistent stigmas against mental health (Bear, Finer, Guo, & Lau, 2014;Stewart, Simmons, & Habibpour, 2012;Uebelacker et al, 2012). School-based programs have the potential to reduce these barriers.…”
mentioning
confidence: 99%